Hubungan Antara Pengelolaan Kondisi Sosio Emosional dan Prestasi Belajar Siswa Pada Pembelajaran IPA Di Kelas V Sekolah Dasar: Hubungan Antara Pengelolaan Kondisi Sosio Emosional dan Prestasi Belajar Siswa Pada Pembelajaran IPA Di Kelas V Sekolah Dasar - Budi Hendrawan (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2016)
The management of socio-emotional condition is part of classroom management, as well as facilities and infrastructure, the management of socio-emotional condition is considered has important role in improving the students’ achievement. The aims of the research are to determine: 1) the management of socio-emotional condition in Class V of Elementary School Cluster 3 Salawu, 2) the students’ achievement in learning science in Grades V of Elementary School Cluster 3 Salawu. The place of this research is in SDN Cluster 3 Salawu of Tasikmalaya regency. The population and sample of this research are the fifth grade students in SDN Cluster 3 Salawu and there are 60 students. The sample of this study used a quota sampling technique. The method used in this research is quantitative associative method with quantitative approach. To collect the data, the researcher used questionnaires and test techniques. The data was collected, processed and analyzed quantitatively with correlation. The results of processing and analyzing data are as follows: 1) The condition of socio-emotional students in learning science in class V SDN Cluster 3 Salawu are in the very good and excellent category. There are 47 (78%) students are in the interval score 90 -120. It can be categorized as very high category. There are 13 (22%) students are in the interval score 70-90 with high category, 2) The students’ achievement in science learning in the fifth class of SDN Force 3 is in the very high, high and moderate category. There are 27 (45%) students in very high category, 25 (41.67%) students in the high category and 8 (13.33%) students in the middle category, 3) there is a relationship between the management of socio-emotional condition and the students’ learning achievement in learning science in the fifth grade of SDN Cluster 3 Salawu. It proved by the correlation between socio-emotional conditions and the students’ learning achievement reached 0.592 and it is in the level of strong enough relationship. The value of the probability or sig. (2-tailed) was 0,000 less than 0.05. According to the provisions: